Images of American Auctones: Between Oficial Records and Hibrid Ficition - Fleck, Gilmei Francisco [UNESP]; Lopes, Rodrigo Smaha (Univ Federal Espirito Santo, 2015)
This article aims at showing - through the contrast between the official documents: Columbus's Journal (1492) and Caminha's Letter (1500), and the Historical Romance genre produced in the Americas - how literature has sought to reveal to society other images of the natives than those produced by Europeans in stereotypical historical documents, which account for biased physical and psychological aspects, devaluing the natives, seen as easy beings to dominate, catechize and enslave. We believe that the literary images of the autochthonous Americans, members of the mestizo and hybrid societies from the nations that were formed on American soil that were overlooked by the hegemonic historical discourse, started having another representativeness in the continent after the advent of the hybrid genre inaugurated by Walter Scott (1771-1832) in 1814, as we seek to demonstrate in this text.
Keywords: Historical Novel; Autochthonous Americans; Americas